2001
DOI: 10.1007/s004010000287
|View full text |Cite
|
Sign up to set email alerts
|

Sural nerve fibre pathology in diabetic patients with mild neuropathy: relationship to pain, quantitative sensory testing and peripheral nerve electrophysiology

Abstract: Nerve fibre pathology is poorly described in diabetic patients with mild neuropathy and has not been adequately related to clinical evaluation, quantitative sensory examination and neurophysiology. Sural nerve myelinated and unmyelinated fibre pathology was morphometrically quantified and related to the presence of pain and conventional measures of neuropathic severity in 15 diabetic patients with mild neuropathy and 14 control subjects. Diabetic patients demonstrated a significant (P<0.01) reduction in myelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(61 citation statements)
references
References 27 publications
0
59
0
2
Order By: Relevance
“…From evaluation of sural nerve biopsies, myelinated nerve fibre density has proven a reliable indicator of neuropathy in patients with diabetes [25]. For the patients with diabetes and carpal tunnel syndrome in this study, we have previously demonstrated significant reduction in myelinated nerve fibre density in the non-compressed posterior interosseous nerve of the forearm, compared with the patients without diabetes with idiopathic carpal tunnel syndrome [26].…”
Section: Discussionmentioning
confidence: 51%
“…From evaluation of sural nerve biopsies, myelinated nerve fibre density has proven a reliable indicator of neuropathy in patients with diabetes [25]. For the patients with diabetes and carpal tunnel syndrome in this study, we have previously demonstrated significant reduction in myelinated nerve fibre density in the non-compressed posterior interosseous nerve of the forearm, compared with the patients without diabetes with idiopathic carpal tunnel syndrome [26].…”
Section: Discussionmentioning
confidence: 51%
“…A reduction in myelinated fibre density is an indicator of mild neuropathy in diabetic patients [11]. A quantifiable association also exists between the magnitude of myelinated nerve fibre loss and a meaningful alteration in neurological and electrophysiological deficits [12].…”
Section: Discussionmentioning
confidence: 99%
“…STZ-induced diabetic mice undergo significant reductions in cutaneous innervation of the hindlimb by 7 weeks after STZ injection, while similar changes in cutaneous innervation have not been observed in rats (Karanth et al, 1990;Christianson et al, 2003a). Thus, the mechanical and chemogenic hypoalgesia in mice is linked to the reduced cutaneous innervation similar to diabetic humans (Bertelsmann et al, 1986;Malik et al, 2001). It is noteworthy that the mechanical hypoalgesia in mice occurs after the appearance of ATF3-positive neurons in the lumbar DRG, suggesting that the behavioral deficits may not emerge until a sufficient number of neurons are affected by diabetes.…”
Section: Diabetes-induced Mechanical Hypoalgesiamentioning
confidence: 96%